The Effect of Hoteling Quality on Patient Loyalty in Private Hospitals of Tehran from Patients\' Viewpoint - Maryam Jafar Tajrishi; Seyed Jamaledin Tabibi; Kamran hajinabi (Tehran University of Medical Sciences, 2018)
Background and Aim: In today's competitive market conditions of hospital industry, in addition to the quality of clinical services, a hospital should also concentrate on Hotelling Services Quality designed for the patient and his entourage. The purpose of this study was to investigate the effect of hoteling quality on patient loyalty. Materials and Methods: The research method of the study was descriptive-survey with an applied goal. The research instrument was a questionnaire whose validity and reliability were verified by face-to-face survey and Cronbachchr('39')s alpha. The sample size according to Cochran formula for unknown population was 385 patients in two private hospitals of Tehran that were randomly selected. The data were analyzed by descriptive and inferential statistics such as multivariate linear regression test. Results: According to the findings of the study at 95% confidence level, the quality of human resources (p<0.001), the quality of hospital welfare services (p<0.001) and the quality of administrative affairs and workflow (p=0.002), the quality of cleaning and sanitation services (p<0.001) and the quality of building and hospital facilities (p=0.033) have a positive effect on patient loyalty. Also, two other dimensions, that is, the quality of hospital equipment and facilities (p=0.317) and the quality of hospital nutrition services (p=0.123) did not have a meaningful effect on patient loyalty. Conclusion: From patientschr('39') perspective, the hotelling quality in the studied hospitals has a direct impact on patient loyalty, and its improvement will increase patients' loyalty in those hospitals.